2013
DOI: 10.18806/tesl.v30i2.1140
|View full text |Cite
|
Sign up to set email alerts
|

Putting Multiliteracies Into Practice: Digital Storytelling for Multilingual Adolescents in a Summer Program

Abstract: In this article we demonstrate how we created a context in which digital storytelling was designed and implemented to teach multilingual middle school students in the summer program sponsored by a local nonprofit organization, the Latin American Association, in a city in the southeastern United States. While implementing the notion of multiliteracies (New London Group, 1996) In this article we demonstrate how we applied the theoretical concept of multiliteracies to a pedagogical practice. We describe how we,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 7 publications
2
43
0
1
Order By: Relevance
“…One of the study's strengths lies in that it reports on the teachers' actual employment of multimodality in the existing curriculum, especially in content area classes, in contrast to previous studies that have described teachers' future lesson plans that embed multimodality (e.g., Thompson, ) or teachers' perceptions about the approach (e.g., Ajayi, ). Moreover, the teachers' orchestration of multiple modes in various in‐class projects and tasks rather than in one common form of multimodal practices (i.e., digital video composing) as explored in many studies (Angay‐Crowder et al., ; Hull & Nelson, ; Miller, ; Rance‐Roney, ) expands the discussion about multimodal practices in in‐school contexts. Last, the study has revealed the notion of intertextuality—ELLs returning to and practicing content and linguistic knowledge repeatedly, yet with a difference—as a useful framework for TESOL educators (Kress, ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the study's strengths lies in that it reports on the teachers' actual employment of multimodality in the existing curriculum, especially in content area classes, in contrast to previous studies that have described teachers' future lesson plans that embed multimodality (e.g., Thompson, ) or teachers' perceptions about the approach (e.g., Ajayi, ). Moreover, the teachers' orchestration of multiple modes in various in‐class projects and tasks rather than in one common form of multimodal practices (i.e., digital video composing) as explored in many studies (Angay‐Crowder et al., ; Hull & Nelson, ; Miller, ; Rance‐Roney, ) expands the discussion about multimodal practices in in‐school contexts. Last, the study has revealed the notion of intertextuality—ELLs returning to and practicing content and linguistic knowledge repeatedly, yet with a difference—as a useful framework for TESOL educators (Kress, ).…”
Section: Resultsmentioning
confidence: 99%
“…The term Multimodal pedagogies covers various forms of communication in learning environments connected to multimodality, or multiple modes, of meaning making, which refers to such things as body language, gestures, activities with visual and audial substances etc., yet, first, with media and technologies. Students may fill in their reports and presentations as creative multiliteracy texts (Angay-Crowder et al 2013). Positive pedagogy (O'Brien & Blue, 2017) affirms that success and positive learning experiences, cognitions and emotions make students flourish at school.…”
Section: Multilingual Education In Support Of the Family Language Policymentioning
confidence: 95%
“…To understand how district training is translated to actual practice and its effects on student learning, we conducted a small case study in one participating 12th‐grade English language arts class in which the teacher is also a DIGICOM trainer. Although DST is used to teach various subjects in the PSUSD, prior work indicated that DST is particularly effective for student learning in English language arts classrooms (Angay‐Crowder, Choi, & Yi, ). On a weekly basis for two months, we observed two classes taught by the same teacher using the same ERWC curriculum for both classes.…”
Section: Benefits Of Dstmentioning
confidence: 99%